Applying Profile Matching Methode to Determine The Best Employees in Educational Institutions - Veti Apriana; Imam Nawawi (Institute of Computer Science (IOCS), 2020)
In every company, the performance evaluation of each employee is very important in order to determine the ability, progress and achievement or performance results of each employee. Performance evaluation is an assessment of the performance of each employee whose results can be used for human resource development, companies and educational institutions. In relation to performance evaluation, it is very close to determining the selection of the best employees who will later be used as benchmarks in companies and educational institutions in providing promotions. Determining the best employee is a difficult decision making, the thing that makes it difficult is the implementation of the limited evaluation time and the number of employees so that the selection of the best employee is only chosen by the manager and the results of the assessment are subjective. Selection of the best employees in this study used the profile matching method, assessment and calculation of GAP values ??based on disciplinary criteria, employee performance and soft skills. The final result of the profile matching method is in the form of a ranking which shows that the higher the ranking is produced, the greater the chance to get an assessment as the best employee. The results showed that the profile matching method can be used in a decision support system to determine the best employees in companies and educational institutions.